2016
DOI: 10.1088/1367-2630/18/6/063014
|View full text |Cite
|
Sign up to set email alerts
|

Wavebreaking-associated transmitted emission of attosecond extreme-ultraviolet pulses from laser-driven overdense plasmas

Abstract: We present a new mechanism of attosecond extreme-ultraviolet (XUV) pulses generation from a relativistic laser-driven overdense plasma surfaces in the wavebreaking regime. Through particle-incell simulations and analysis, we demonstrate that the observed ultrashort XUV emission for the parameters we considered is predominantly due to a strong plasma-density oscillation subsequent to wavebreaking. The coupling of the strong density variation and the transverse fields in the front surface layer gives rise to the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…[22]), the forward emission mechanism is fundamentally different from that associated with wave breaking as discussed in Refs. [27,34].…”
Section: Cse From Electron Bunchesmentioning
confidence: 99%
“…[22]), the forward emission mechanism is fundamentally different from that associated with wave breaking as discussed in Refs. [27,34].…”
Section: Cse From Electron Bunchesmentioning
confidence: 99%
“…Chen et al also investigated the effects of the density gradient of plasma foil targets and those of multi dimensions on the XUV pulse generation. [17] In summary, the electron dynamics and the associated generation of attosecond EM pulses have been studied with the wavebreaking process when one intense laser pulse normally irradiates on a dense plasma foil target. Two distinct electron bunches closely related to the wavebreakings are observed to emit attosecond pulses in both the reflection and the transmission.…”
Section: Figure 3(b)mentioning
confidence: 99%
“…[9,13,15] A complicated generation process of attosecond XUV pulses is reported as the wavebreaking associated transmitted emission (WTE) by Chen et al in the study of a relativistic laser pulse irradiating on an overdense plasma surface. [17] It is found that the strong wavebreaking process of the plasma generates XUV pulses in the transmitted direction. However, the detailed process of the EM pulse generation associated with the wavebreaking is not discovered in that work.…”
mentioning
confidence: 99%
“…However, the limitation on laser intensity implies that the emitted harmonic pulse energy is also limited. One way to break through this limitation is to generate attosecond pulses using solid target [8][9][10][11][12][13][14][15][16]. After irradiated by an intense laser, the target becomes plasmas and can withstand laser intensity of 10 18 W cm −2 and even higher.…”
Section: Introductionmentioning
confidence: 99%